2021
DOI: 10.1002/brb3.1780
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in adult social, cognitive, and affective behavioral deficits following neonatal phlebotomy‐induced anemia in mice

Abstract: While multiple factors contribute to this increased neurodevelopmental risk, the degree of neonatal anemia is one that is controllable by the healthcare team. However, two randomized trials that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…The finding that anemia alters brain inflammatory gene expression is unique and concerning if translatable to human infants because of the deleterious effect of inflammation on the developing brain. The findings of the study provide several potential mechanisms to explain the sex-dependent differences in neurobehavioral performance reported in this model 12 and in clinical studies of anemic preterm infants. 23 – 25 …”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…The finding that anemia alters brain inflammatory gene expression is unique and concerning if translatable to human infants because of the deleterious effect of inflammation on the developing brain. The findings of the study provide several potential mechanisms to explain the sex-dependent differences in neurobehavioral performance reported in this model 12 and in clinical studies of anemic preterm infants. 23 – 25 …”
Section: Discussionmentioning
confidence: 75%
“…We previously demonstrated that neonatal PIA negatively affects learning, memory, and social behavior in adulthood and does so differently between males and females. 12 In the current study, large-scale dysregulation in gene pathways and networks important for neurodevelopment was present in mPIA and sPIA males and sPIA females. Both mPIA and sPIA males showed a similar degree of dysregulation of genes critical for embryonic, organismal, and tissue development in the hippocampus ( Supplementary Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the clinical population, there is evidence supporting sexspecific outcomes for iron-deficient individuals or its treatment during early life, including differential effects on fecal microbiota (5), brain development (6), verbal fluency (7), and risks of cognitive disorders such as schizophrenia (2). Sex-specific physiologic and behavioral effects are also observed in preclinical models (8)(9)(10)(11). Early postnatal ID anemia causes sex-specific neuroinflammatory responses (8), seizure vulnerability (9), social and affective behavioral abnormality (10), and vasculature dysfunction (11).…”
Section: Introductionmentioning
confidence: 99%